(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Diagnosing and treating supraventricular tachyarrhythmias such as atrial flutter, atrioventricular nodal re-entrant tachycardia (AVNRT), and atrioventricular re-entrant tachycardia (AVRT) is difficult. Short-acting antiarrhythmic drugs like adenosine are frequently used to stop re-entrant tachycardias and identify the underlying causes of arrhythmias. Objective: This study evaluates adenosine’s therapeutic effectiveness in stopping atrial flutter, AVRT, and AVNRT, and the ability of adenosine to distinguish between them was assessed. Methodology: In this single-arm interventional trial, individuals with persistent supraventricular tachyarrhythmias were enrolled in a tertiary care hospital. Intravenous adenosine was given in increments until the arrhythmia stopped or the diagnosis was clear. Clinical and electrophysiological reactions to adenosine were documented to distinguish between AVNRT, AVRT, and atrial flutter. Results: Palpitations were the most prevalent symptom (94%), followed by dizziness (62%), chest pain (58%), and fatigue (50%). The mean heart rate was 154.7 bpm, with systolic and diastolic blood pressures averaging 124.24 mmHg and 79.5 mmHg, respectively. Oxygen saturation remained stable at 97.78%. Adenosine was administered at 6 mg (56%), 12 mg (38%), and 18 mg (6%), with AVNRT being the most common diagnosis (54%), followed by AVRT (30%) and atrial flutter (12%). Adenosine demonstrated high diagnostic accuracy (AVNRT: 92.59%, AVRT: 93.33%, atrial flutter: 83.33%) and therapeutic success (AVNRT: 85.18%, AVRT: 86.67%). Conversion to sinus rhythm was fastest in AVNRT (15.44 ± 4.98 sec) compared to AVRT (18.57 ± 6.50 sec). Common side effects included flushing (42%), chest pain (26%), and dizziness (22%). Post-treatment, 72% required no further intervention, while 20% needed beta-blockers. Adenosine was 89.75% accurate for diagnosis and 68.39% effective for treatment. Conclusion: Adenosine is highly effective in diagnosing and terminating SVT, particularly AVNRT and AVRT, with a favorable safety profile. While most patients responded to initial doses, individualized management remains crucial due to variable treatment responses and side effects.